Effects of silicon and drought stress on biochemical characteristics of leaves of upland rice cultivars - Mauad, Munir; Crusciol, Carlos Alexandre; Nascente, Adriano; Grassi Filho, Hélio; Lima, Giuseppina (Revista Ciência Agronômica, 2016)
Silicon (Si) has beneficial effects on many crops, mainly under biotic and abiotic stress. Silicon can affect biochemical, physiological, and photosynthetic processes and, consequently, reduce drought stress. However, the effects of Si on rice (Oryza sativa L.) plants under drought stress are not well known. The objective of this study was to evaluate the effects of supplemental Si on proline content and peroxidase activity in upland rice plants in the presence and absence of drought stress. The experiment was conducted under greenhouse conditions and was arranged in completely randomized blocks in a 2 × 2 x 2 factorial scheme. Treatments comprised combinations of (1) presence or absence of Si supply (0 or 350 kg ha-1 of Si), (2) presence or absence of a water deficit (−0.050 MPa or −0.025 MPa soil water potential values, respectively), and (3) two upland rice cultivars: Caiapo (traditional type) and Maravilha (modern type), with eight replications. Under water stress conditions, silicon fertilization reduced the proline content in the vegetative and reproductive phases of upland rice plants and increased peroxidase activity in the plants’ reproductive phase, which could be indicative of stress tolerance.